Optical versus electrical dispersion compensation: role of timing jitter - Pinto, AN
This paper calculates timing jitter in intensity-modulated/direct detection lightwave systems in which chromatic dispersion is compensated in the optical domain and in systems where the effects of chromatic dispersion are mitigated by means of electrical equalization at the receiver. The authors focus on a linear communication channel and derive a new expression for the timing jitter after the photodetector using frequency-domain analysis. It shows that timing jitter depends cubically on link length when dispersion is compensated in the electrical domain. In contrast, when dispersion is fully compensated optically, timing jitter depends only linearly on the link length. A new expression for the optimum timing jitter in the presence of residual dispersion is also presented.